QUASIINVARIANT GAUSSIAN MEASURES FOR ONE-DIMENSIONAL HAMILTONIAN PARTIAL DIFFERENTIAL EQUATIONS. (2nd December 2015) - TZVETKOV, NIKOLAY
Abstract : We prove the quasiinvariance of Gaussian measures (supported by functions of increasing Sobolev regularity) under the flow of one-dimensional Hamiltonian partial differential equations such as the regularized long wave, also known as the Benjamin–Bona–Mahony (BBM) equation.